ОЗЕРА НИЖНЕГО АМУРА. СТАТЬЯ 1. ГЕОГРАФИЯ И ТИПЫ ОЗЕР - Уфимцев Г.Ф.; Щетников А.А.; Алексеенко С.Н. (My University, 2005)
Lakes of the Lower Amur basin are numerous and diverse. Together with the north-west of the Russian Plain and plateau Putorana they consist one of the three main Lake Countries of Russia. The paper concerns their classification and distribution features.
Keywords: 551.435.38>556.557(-925.17)